A Strong X-Ray Polarization Signal from the Magnetar 1RXS J170849.0-400910 - Zane Silvia; Taverna Roberto; González-Caniulef Denis; Muleri Fabio; Turolla Roberto; Heyl Jeremy; Uchiyama Keisuke; Ng Mason; Tamagawa Toru; Caiazzo Ilaria; Di Lalla Niccolò; Marshall Herman L.; et al. (IOP Publishing Ltd, 2025)
Magnetars are the most strongly magnetized neutron stars, and one of the most promising targets for X-ray polarimetric measurements. We present here the first Imaging X-ray Polarimetry Explorer observation of the magnetar 1RXS J170849.0-400910, jointly analyzed with a new Swift observation and archival NICER data. The total (energy- and phase-integrated) emission in the 2-8 keV energy range is linerarly polarized, at a similar to 35% level. The phase-averaged polarization signal shows a marked increase with energy, ranging from similar to 20% at 2-3 keV up to similar to 80% at 6-8 keV, while the polarization angle remains constant. This indicates that radiation is mostly polarized in a single direction. The spectrum is well reproduced by a combination of either two thermal (blackbody) components or a blackbody and a power law. Both the polarization degree and angle also show a variation with the spin phase, and the former is almost anticorrelated with the source counts in the 2-8 and 2-4 keV bands. We discuss the possible implications and interpretations, based on a joint analysis of the spectral, polarization, and pulsation properties of the source. A scenario in which the surface temperature is not homogeneous, with a hotter cap covered by a gaseous atmosphere and a warmer region in a condensed state, provides a satisfactory description of both the phase- and energy-dependent spectro-polarimetric data. The (comparatively) small size of the two emitting regions, required to explain the observed pulsations, does not allow to reach a robust conclusion about the presence of vacuum birefringence effects.